PERAN STRATEGI ORGANISASI KEPEMUDAAN KIPAN DALAM MENJAWAB TANTANGAN NARKOBA DI KALANGAN PEMUDA INDONESIA - Nabia Dilla Derma Pratiwi; Rizki Septia Pratiwi; Qitallya Adinda Zahrani; Ana Mentari; Rima Yuni Saputri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The young generation has a role as an agent of change in realizing the progress of the nation. However, this role can be threatened by the existence of drug abuse which is increasingly widespread. This article aims to examine the role of the youth organization, the KIPAN in efforts to prevent drug abuse among young people, especially in Lampung province. Through a descriptive qualitative approach and in-depth interviews with the general chairman of KIPAN, this study describes the educational and participatory strategies implemented by the organization such as the use of social media, training, and direct socialization to schools. The results of the study indicate that the active involvement of young people in the organization is able to provide reinforcement for preventive efforts through the dissemination of emotional support information, and strengthening social control in the community.